1992
DOI: 10.1254/jjp.58.157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfhydryl-Related Compounds on Indomethacin-Induced Gastric Lesions in Rats: Role of Endogenous Sulfhydryls in the Pathogenesis.

Abstract: ABSTRACT-The role of mucosal sulfhydryl (SH) in the pathogenesis of indomethacin induced gastric lesions was investigated in rats. Indomethacin (25 mg/kg, s.c.) caused high-amplitude gastric contractions, resulting in linear hemorrhagic lesions in the cor pus mucosa within 4 hr, but did not induce any changes in the mucosal SH levels. These lesions were prevented significantly by prior s.c. administration of cysteamine, glutathione (GSH) or diethylmaleate (DEM), irrespective of whether the mucosal SH was incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…Amifostine alone, s.c. or i.p., increased the NP-SH concentration in gastric tissue and also reversed the decrease in NP-SH concentration in the gastric tissue induced by indomethacin ( Table 2). Our data are in accordance with the literature; Ueshima et al [21] demonstrated that exogenous glutathione (GSH), a sulfhydryl compound, inhibits indomethacin-induced gastric damage. Szabo et al [22] showed that substances containing sulfhydryl radicals, such as dimercaprol, cysteamine, and dimercaptosuccinic acid, work in the protection of the gastric mucosa in a manner similar to that of prostaglandins, and that sulfhydryl group blockers, such as diethylmaleate and iodoacetamide, reverse the gastric protective effect of PGF 2α .…”
Section: Discussionsupporting
confidence: 93%
“…Amifostine alone, s.c. or i.p., increased the NP-SH concentration in gastric tissue and also reversed the decrease in NP-SH concentration in the gastric tissue induced by indomethacin ( Table 2). Our data are in accordance with the literature; Ueshima et al [21] demonstrated that exogenous glutathione (GSH), a sulfhydryl compound, inhibits indomethacin-induced gastric damage. Szabo et al [22] showed that substances containing sulfhydryl radicals, such as dimercaprol, cysteamine, and dimercaptosuccinic acid, work in the protection of the gastric mucosa in a manner similar to that of prostaglandins, and that sulfhydryl group blockers, such as diethylmaleate and iodoacetamide, reverse the gastric protective effect of PGF 2α .…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that lipid peroxidation might not be an important process in the development of mucosal lesions in this model. Two additional studies have also shown that lipid peroxidation is not involved in the pathogenesis of acute gastric mucosal injury caused by indomethacin [20] and that mucosal sulfhydryl levels have no relation to the ulcerogenicity of indomethacin [21] and these results agree with our data.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance to literature, this present study also showed that oral administration of indomethacin (20 mg/kg) results in gastric hemorrhagic erosions, increase in neutrophil infiltration [2,18] and decrease in NP-SH concentration in the gastric tissue [19,20]. Recently, we demonstrated that LPS, at a dose 300 lg/kg, completely eliminated indomethacin-induced gastric damage and neutrophil infiltration.…”
Section: Discussionsupporting
confidence: 92%
“…Our group demonstrated that a SH compound (amifostine) protects indomethacininduced gastric damage by an increase in the NP-SH group in the gastric mucosa [20]. Ueshima [19] demonstrated that exogenous glutathione (GSH) inhibits indomethacininduced gastric damage and that substances containing sulfhydryl radicals, such as dimercaprol, cysteamine and dimercaptosuccinic acid, work in the protection of the gastric mucosa in the same way prostaglandins do, and that sulfhydryl group blockers, such as diethylmaleate and iodoacetamide, reverse the gastric protective effect of PGF 2a [17]. Then, we suggested that LPS gastroprotective effect against indomethacin-induced gastric damage could be secondary to an increase in gastric GSH concentration.…”
Section: Discussionmentioning
confidence: 94%